Role of the CD4 Down-Modulation Activity of Nef in HIV-1 Infectivity - Doria, Margherita (Current HIV Research, 2011)
The regulatory Nef protein of HIV-1/2 and SIV is required for high viral replication and disease progression, thus represents a very attractive therapeutic target. Because of the multi-functional nature of the Nef protein, it is unclear which of the several Nef activities are most crucial in vivo for the outcome of viral infection. Some findings indicate that the CD4 down-regulation activity of Nef is critical for viral infectivity as well as for progression to immunodeficiency. On the other hand, more recent evidences suggest that CD4 targeting and stimulation of infectivity are two separate functions of Nef. This controversial issue will be discussed here in the light of the latest findings.
Keywords: HIV-1